ВСТАНОВЛЕННЯ УСТАЛЕНОГО РЕЖИМУ В МЕРЕЖІ З УМОВНО ДВАНАДЦЯТИФАЗНИМ КЕРОВАНИМ КОМПЕНСАЦІЙНИМ ПЕРЕТВОРЮВАЧЕМ ПРИ ПОСЛІДОВНОМУ ПРЯМОМУ ПУСКУ ВІД НЕЇ ГРУПИ ПОТУЖНИХ АСИНХРОННИХ МАШИН - Блінов, І.В.; Чиженко, О.І.; Рибіна, О.Б. (Інститут електродинаміки Національної академії наук України, 2025)
The process of setting steady-state values of currents and voltages in the circuit of a conditionally twelve-phase controlled compensating converter (CTCCC), which is powered by a 6 kV electrical network, in the mode of sequential direct start from it of a group of powerful (8 MW) asynchronous machines (AM) is considered. Time diagrams of transient values of currents and voltages of the CTCCC elements in this mode are constructed.